2014
DOI: 10.1017/s1759078714000993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Au metal–metal contacts in a lateral actuated RF MEMS switch

Abstract: This paper reports on the ohmic contacts of an radio-frequency micro-electro-mechanical-system (RF MEMS) switch. The structure of the MEMS is described briefly to give information about the organization of the switch device. The most significant performance data are reported, indicating very low actuation voltage below 5 V, switching time of <10 µs and good RF performance for frequencies up to 5 GHz. Since the contact performance is a key for excellent RF performance in the actuated state and for high relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Markus et al (2014) have reported that they have designed a MEMS switch which requires very low pull in voltage as 5V and switching time is less than 10 µs at 5 Ghz. The designed switch is very much usable for RF applications [14]. K. Guha et al (2015), have proposed meander-based switch made up of Aluminum membrane and the study was done for providing very less switching time as 3 µs for actuation voltage of 5V [15].…”
Section: Introductionmentioning
confidence: 99%
“…Markus et al (2014) have reported that they have designed a MEMS switch which requires very low pull in voltage as 5V and switching time is less than 10 µs at 5 Ghz. The designed switch is very much usable for RF applications [14]. K. Guha et al (2015), have proposed meander-based switch made up of Aluminum membrane and the study was done for providing very less switching time as 3 µs for actuation voltage of 5V [15].…”
Section: Introductionmentioning
confidence: 99%